Beyond the Red Queen syndrome: CRM technology and building material suppliers - Love, Peter; Edwards, D.; Standing, C.; Irani, Z. (Emerald Group Publishing, 2009)
Purpose – Many businesses operating in the construction and engineering sector have been trying to respond to the demands being imposed on them by utilising information technology applications such as CRM and ERP, but immediate benefits and improvements in business performance have not been forthcoming. This paper aims to provide building material suppliers with the underlying knowledge to improve their business performance and customer relationships. Design/methodology/approach – A structural model that examines the following critical success factors of implementing CRM was constructed: operational and strategic benefits, knowledge top management support, technological readiness, and management capabilities. The model was tested using a questionnaire survey and randomly distributed to 150 building material suppliers. Findings – A sample 72 building material suppliers was obtained. Using the evaluation technique of partial least squares the analysis fundamentally revealed that CRM technological initiatives are successful when adequate top management support and accurate knowledge management capabilities, supported by a suitable IT structure, (measured by technological readiness) are in place. Material suppliers, as well as other organisations operating in the construction and engineering sector, considering the implementation of a CRM strategy can utilise these results to become better acquainted with CRM applications.Practical implications – To reap the rewards of CRM technological initiatives material suppliers need to develop a strategy for its implementation. Part of this strategy should be determining the factors that will influence its successful implementation and then develop a plan to address these issues. The results provide valuable insights into the critical success factors of CRM technological initiatives.Originality/value – The paper shows that managers should develop strategies based upon critical success factors to maximise the benefits of their CRM application.